2018
DOI: 10.4172/2472-4971.1000163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Various Diagnostic Markers for Early Detection of Neonatal Sepsis

Abstract: Background: Prompt diagnosis of neonatal sepsis at an early stage is essential to initiate therapy as well as to avoid unnecessary usage of antibiotics. Therefore the search for an ideal marker including antigenic expression on inflammatory cells is still continuing. The aim of the study was to identify an ideal early laboratory marker for diagnosis of neonatal sepsis. Methods: The samples sent for complete blood count were processed for Haematologic Scoring System (HSS) and flow cytometry for expression of CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…al. (24), it was found that the commonly detected organisms were Staphylococcus aureus in 22.5% of the patients, Klebsiella in 18.6% and Acinetobacter (12.8%). From the variable results obtained from different studies, it is evident that the causative organisms of neonatal septicemia vary from nursery to nursery, between different geographical areas and in the same catchment area.…”
Section: Resultsmentioning
confidence: 94%
“…al. (24), it was found that the commonly detected organisms were Staphylococcus aureus in 22.5% of the patients, Klebsiella in 18.6% and Acinetobacter (12.8%). From the variable results obtained from different studies, it is evident that the causative organisms of neonatal septicemia vary from nursery to nursery, between different geographical areas and in the same catchment area.…”
Section: Resultsmentioning
confidence: 94%